1979
DOI: 10.1111/j.1399-3054.1979.tb02621.x
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine and Spermidine in Peas: Effeets on Nitrogen Source and Potassium Supply

Abstract: Free and total putrescine and, to a lesser extent, spemidine accumulate in both roots and shoots of peas in response to potas stum deficiency and ammomnium supply. Free putrescine responds more sensitively than total putreseine to variatioin of nutrients. Accumulation of putrescine is more pronounced in the roots than in the shoots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Further metabolic studies established that radiolabeled ornithine was converted to putrescine more rapidly in ammonium-fed seedlings, that the rate of agmatine metabolism to putrescine was accelerated under these conditions, and that the degree of putrescine oxidation by diamine oxidase was considerably lower under conditions of ammonium as compared with nitrate nutrition (Le Rudulier andGoas 1974, 1977). A similar effect of ammonium on putrescine accumulation was found in other plants, including tomato, tobacco, pea, petunia and pepper (Hohlt et al 1970, Klein et al 1979). Since ammonium feeding leads to acidification of the medium, it was questioned whether medium acidification was the direct cause for putrescine accumulation.…”
Section: Introductionsupporting
confidence: 60%
“…Further metabolic studies established that radiolabeled ornithine was converted to putrescine more rapidly in ammonium-fed seedlings, that the rate of agmatine metabolism to putrescine was accelerated under these conditions, and that the degree of putrescine oxidation by diamine oxidase was considerably lower under conditions of ammonium as compared with nitrate nutrition (Le Rudulier andGoas 1974, 1977). A similar effect of ammonium on putrescine accumulation was found in other plants, including tomato, tobacco, pea, petunia and pepper (Hohlt et al 1970, Klein et al 1979). Since ammonium feeding leads to acidification of the medium, it was questioned whether medium acidification was the direct cause for putrescine accumulation.…”
Section: Introductionsupporting
confidence: 60%
“…Osmotic stress has been reported to stimulate polyamine accumulation in plants (Flores and Galston, 1982, 1984a, and 1984b. The plants with toxic symptoms under stress of potassium deficiency usually accumulate high concentration of putrescine (Corey and Barker, 1989;Klein et al, 1979;Smith, 1973). A previous study also indicated that high putrescine Downloaded by [Cornell University Library] at 16:17 19 November 2014 concentration from stressed plants was associated with high ammonium accumulation and ethylene evolution (Feng, 1992).…”
Section: Discussionmentioning
confidence: 92%
“…Polyamines are involved in development, senescence, and stress responses of plants (Galston and Sawhney 1990;Kumar et al 1997). Additionally, putrescine accumulation in response to K deficiency has been reported in other plant species (Klein et al 1979;Smith et al 1982;Adams et al 1990;Sung et al 1994). Thus, our results indicate that -K stress response is similar in gentian, even in explants culture.…”
Section: Metabolite Profiles Of K and P Deficiencymentioning
confidence: 92%